Additive process for patterned metallized conductive tracks on cotton with applications in smart textiles. Issue 2 (1st February 2018) - Wills, K. A.; Krzyzak, K.; Bush, J.; Ashayer-Soltani, R.; Graves, J. E.; Hunt, C.; Cobley, A. J.
Abstract: The selective patterning of silver nanoparticles by a patent pending process to act as a catalyst for metallization with electroless copper was explored on cotton, with a view towards application in the wearable technology sector. Whole area coverage or tracks serving as point-to-point connections were achieved by depositing the catalyst via spraying, or in more controlled manner using a microdispenser, respectively. Optimization of the catalyst deposition is described, including substrate characterization via contact angle, FTIR and surface charge measurement. The effects of the copper plating bath temperature and dwell time in the plating bath are examined. With plating times as short as 10 min, samples of good conductivity (sheet resistance, R = <10 Ω/sq) and consistency were produced. A higher or lower plating temperature (compared to supplier recommended conditions) increased or reduced the amount of copper deposited, respectively. The technology was used to produce well-defined conductive tracks on cotton with widths between 1.5 and 4.0 mm.